Asymmetric allylic alkylation of Morita–Baylis–Hillman carbonates with α-fluoro-β-keto esters - Yan, Lin; Han, Zhiqiang; Zhu, Bo; Yang, Caiyun; Tan, Choon-Hong; Jiang, Zhiyong (Beilstein Journal of Organic Chemistry, 2013)
In the presence of a commercially available Cinchona alkaloid as catalyst, the asymmetric allylic alkylation of Morita–Baylis–Hillman carbonates, with α-fluoro-β-keto esters as nucleophiles, have been successfully developed. A series of important fluorinated adducts, with chiral quaternary carbon centres containing a fluorine atom, was achieved in good yields (up to 93%), with good to excellent enantioselectivities (up to 96% ee) and moderate diastereoselectivities (up to 4:1 dr).
Keywords: allylic alkylation; asymmetric catalysis; fluorine; fluoro-β-keto esters; Morita–Baylis–Hillman carbonates; natural product

(untitled) - O’Hagan, D. (Chem. Soc. Rev., 2008)

Organofluorine Compounds: Chemistry and Applications - Hiyama, T. (Springer, 2000)

Organo-fluorine Chemisry - Uneyama, K. (Blackwell, 2006)

Organofluorine Compounds in Medicinal Chemistry and Biomedical Applications - Filler, R.; Kobayashi, Y.; Yagupolskii, L. M. (Elservier, 1993)

(untitled) - Rios, R. (Catal. Sci. Technol., 2012)

(untitled) - Liu, T.-Y.; Xie, M.; Chen, Y.-C. (Chem. Soc. Rev., 2012)

(untitled) - Cho, C.-W.; Krische, M. J. (Angew. Chem., Int. Ed., 2004)

(untitled) - van Steenis, D. J. V. C.; Marcelli, T.; Lutz, M.; Spek, A. L.; van Maarseveen, J. H.; Hiemstra, H. (Adv. Synth. Catal., 2007)

(untitled) - Jiang, Y.-Q.; Shi, Y.-L.; Shi, M. (J. Am. Chem. Soc., 2008)

(untitled) - Cui, H.-L.; Peng, J.; Feng, X.; Du, W.; Jiang, K.; Chen, Y.-C. (Chem.–Eur. J., 2009)

(untitled) - Jiang, K.; Peng, J.; Cui, H.-L.; Chen, Y.-C. (Chem. Commun., 2009)

(untitled) - Cui, H.-L.; Huang, J.-R.; Lei, J.; Wang, Z.-F.; Chen, S.; Wu, L.; Chen, Y.-C. (Org. Lett., 2010)

(untitled) - Furukawa, T.; Nishimine, T.; Tokunaga, E.; Hasegawa, K.; Shiro, M.; Shibata, N. (Org. Lett., 2011)

(untitled) - Li, Y.; Liang, F.; Li, Q.; Xu, Y.-C.; Wang, Q.-R.; Jiang, L. (Org. Lett., 2011)

(untitled) - Yang, W.; Wei, X.; Pan, Y.; Lee, R.; Zhu, B.; Liu, H.; Yan, L.; Huang, K.-W.; Jiang, Z.; Tan, C.-H. (Chem.–Eur. J., 2011)

(untitled) - Furukawa, T.; Kawazoe, J.; Zhang, W.; Nishimine, T.; Tojunaga, E.; Matsumoto, T.; Shiro, M.; Shibata, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Company, X.; Valero, G.; Ceban, V.; Calvet, T.; Font-Bardía, M.; Moyano, A.; Rios, R. (Org. Biomol. Chem., 2011)

(untitled) - Yang, W.; Tan, D.; Li, L.; Han, Z.; Yan, L.; Huang, K.-W.; Tan, C.-H.; Jiang, Z. (J. Org. Chem., 2012)

(untitled) - Tong, G.; Zhu, B.; Lee, R.; Yang, W.; Tan, D.; Yang, C.; Han, Z.; Yan, L.; Huang, K.-W.; Jiang, Z. (J. Org. Chem., 2013)

(untitled) - Cho, C.-W.; Kong, J.-R.; Krische, M. J. (Org. Lett., 2004)

(untitled) - Park, H.; Cho, C.-W.; Krische, M. J. (J. Org. Chem., 2006)

(untitled) - Cui, H.-L.; Feng, X.; Peng, J.; Lei, J.; Jiang, K.; Chen, Y.-C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Huang, J.-R.; Cui, H.-L.; Lei, J.; Sun, X.-H.; Chen, Y.-C. (Chem. Commun., 2011)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Eur. J. Org. Chem., 2011)

(untitled) - Lin, A.; Mao, H.; Zhu, X.; Ge, H.; Tan, R.; Zhu, C.; Cheng, Y. (Chem.–Eur. J., 2011)

(untitled) - Trost, B. M.; Tsui, H.-C.; Toste, F. D. (J. Am. Chem. Soc., 2000)

(untitled) - Kim, J. N.; Lee, H. J.; Gong, J. H. (Tetrahedron Lett., 2002)

(untitled) - Feng, X.; Yuan, Y.-Q.; Jiang, K.; Chen, Y.-C. (Org. Biomol. Chem., 2009)

(untitled) - Hu, Z.; Cui, H.; Jiang, K.; Chen, Y. (Sci. China, Ser. B: Chem., 2009)

(untitled) - Zhu, B.; Yan, L.; Pan, Y.; Lee, R.; Liu, H.; Han, Z.; Huang, K.-W.; Tan, C.-H.; Jiang, Z. (J. Org. Chem., 2011)

(untitled) - Hong, L.; Sun, W.; Liu, C.; Zhao, D.; Wang, R. (Chem. Commun., 2010)

(untitled) - Sun, W.; Hong, L.; Liu, C.; Wang, R. (Org. Lett., 2010)

(untitled) - Deng, H.-P.; Shi, M. (Eur. J. Org. Chem., 2012)

(untitled) - Lin, A.; Mao, H.; Zhu, X.; Ge, H.; Tan, R.; Zhu, C.; Cheng, Y. (Adv. Synth. Catal., 2011)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Peng, J.; Huang, X.; Jiang, L.; Cui, H.-L.; Chen, Y.-C. (Org. Lett., 2011)

(untitled) - Wang, B.; Comany, X.; Li, J.; Moyano, A.; Rios, R. (Tetrahedron Lett., 2012)

(untitled) - Jiang, Z.; Pan, Y.; Zhao, Y.; Ma, T.; Lee, R.; Yuang, Y.; Huang, K.-W.; Wong, M. W.; Tan, C.-H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Pan, Y.; Zhao, Y.; Ma, T.; Yang, Y.; Liu, H.; Jiang, Z.; Tan, C.-H. (Chem.–Eur. J., 2010)